Nonoxynol-9 use, genital ulcers, and HIV infection in a cohort of sex workers. - Weir, S S (1995)
OBJECTIVES--To measure the associations between use of nonoxynol-9 (N-9) and incidence of genital ulcers, and incident ulcers and HIV seroconversion. METHODS--In a study of barrier contraceptive use and HIV infection, 273 female sex workers used condoms and 100 mg N-9 suppositories, and recorded sexual activity on coital logs. Genital ulcers were diagnosed clinically at monthly clinic visits. HIV infection was diagnosed by ELISA and Western blot. We calculated ulcer incidence rates by level of N-9 use. A nested matched case-control analysis assessed the effect of ulcers on HIV acquisition. RESULTS--More frequent N-9 use was not associated with genital ulcers and may have been protective against the lesions. Ulceration was not a strong risk factor for HIV acquisition in this study (odds ratio 1.1; 95% confidence interval 0.3-3.5). CONCLUSIONS--Frequent use of N-9 can cause genital irritation and ulceration. Ulcers, in turn, may be risk factors for HIV acquisition. This study, however, did not find an association between N-9 use and ulcers, nor between ulcers and HIV. There is probably a threshold of N-9 use frequency or dose below which the risk of ulceration is minimal. Ulcers due to infectious causes may have been prevented by N-9 use in this cohort.